Nitrogen fertilization in the intercropping of corn with two Brachiaria species in a no‑tillage system - Costa, Nídia Raquel; Andreotti, Marcelo; Gameiro, Roberta de Aquino; Pariz, Cristiano Magalhães; Buzetti, Salatiér; Lopes, Keny Samejima Mascarenhas (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate grain and forage yield of the intercropping of corn with Brachiaria species (2008/2009 and 2009/2010 crop seasons), subjected to nitrogen topdressing rates in a no tillage system. A completely randomized block design was used, with four replicates, in a 2x5 factorial arrangement, with two Brachiaria species (Urochloa brizantha 'Xaraés' and U. ruziziensis) and five N topdressing rates: 0, 50, 100, 150, and 200 kg ha‑1. The following were evaluated: indirect readings of leaf-chlorophyll content (Falker chlorophyll index, ICF), macronutrient content in leaves, yield components and grain yield of corn, and forage dry mass yield after intercropping. It was observed that the species U. ruziziensis was more competitive with corn in intercropping, providing lower nutritional content and ICF in both evaluated seasons. Vegetative growth, yield components, and grain yield of corn were not affected by the intercrops. Nitrogen topdressing fertilization linearly increases the weight of 100 grains (2008/2009 season), and all yield components and grain yield (2009/2010 season).